(untitled) (Veterinary Science, 2017)
The present article reviews the latest information of the endothelial organs. The endothelium is a thin layer of cells that recover the lumen of the blood vessels, and in the human being represent an area of approximately 400 m2 and weight 1500 g with capacity of secretion of either microormacro molecules.